Structure and physico-chemical properties of silica gels doped with optically activated Er3+ ions by sol-gel process - Long, Nguyen Viet; Xuan Thao, Du Thi; Chien, Nguyen Duc; Binh, Pham Thanh (Vietnam Journal of Chemistry, 2014)
This paper is devoted  to the study of the relationship between structure and optical properties of silica glasses doped with optically active Er3+ ions and reported the influence of the suitably selected heat treatment on the optical properties of silica glasses. The physico-chemical properties of Er3+doped silica are presented, which has been related with the effects of hydroxyl groups on the luminescence property  of Er3+ in the host matrix of silica